Thermodynamic analysis of direct steam reforming of ethanol in molten carbonate fuel cell - Silveira, José Luz [UNESP]; Souza, Antonio Carlos Caetano de [UNESP]; Silva, Márcio Evaristo da [UNESP] (Asme-amer Soc Mechanical Eng, 2008)
Fuel cell as molten carbonate fuel cell (MCFC) operates at high temperatures. Thus, cogeneration processes may be performed, generating heat for its own process or for other purposes of steam generation in the industry. The use of ethanol is one of the best options because this is a renewable and less environmentally offensive fuel, and is cheaper than oil-derived hydrocarbons, as in the case of Brazil. In that country, because of technical, environmental, and economic advantages, the use of ethanol by steam reforming process has been the most investigated process. The objective of this study is to show a thermodynamic analysis of steam reforming of ethanol, to determine the best thermodynamic conditions where the highest volumes of products are produced, making possible a higher production of energy, that is, a more efficient use of resources. To attain this objective, mass and energy balances were performed. Equilibrium constants and advance degrees were calculated to get the best thermodynamic conditions to attain higher reforming efficiency and, hence, higher electric efficiency, using the Nernst equation. The advance degree (according to Castellan 1986, Fundamentos da Fisica/Quimica, Editora LTC, Rio de Janeiro, p. 529, in Portuguese) is a coefficient that indicates the evolution of a reaction, achieving a maximum value when all the reactants' content is used of reforming increases when the operation temperature also increases and when the operation pressure decreases. However, at atmospheric pressure (1 atm), the advance degree tends to stabilize in temperatures above 700 degrees C; that is, the volume of supplemental production of reforming products is very small with respect to high use of energy resources necessary. The use of unused ethanol is also suggested for heating of reactants before reforming. The results show the behavior of MCFC. The current density, at the same tension, is higher at 700 degrees C than other studied temperatures such as 600 and 650 degrees C. This fact occurs due to smaller use of hydrogen at lower temperatures that varies between 46.8% and 58.9% in temperatures between 600 and 700 degrees C. The higher calculated current density is 280 mA/cm(2). The power density increases when the volume of ethanol to be used also increases due to higher production of hydrogen. The highest produced powers at 190 mA/cm(2) are 99.8, 109.8, and 113.7 mW/cm(2) for 873, 923, and 973 K, respectively. The thermodynamic efficiency has the objective to show the connection among operational conditions and energetic factors, which are some parameters that describe a process of internal steam reforming of ethanol.
Keywords: Steam reforming of Ethanol; DIR-MCFC; Technical analysis; Electricity generation